The relationship between whatsapp acceptance and job performance among employee in Perbadanan Usahawan Nasional Berhad (PUNB)/ Nor Nabilah Yusof - Yusof, Nor Nabilah (2019)
WhatsApp Application is a common communication software that had been used nowadays. ICT has become necessary and being a part of our life due to new era and advancement of new technology needed. The development of existing a new technology has made an impact on the individual as well as to the firm job performance. The used of this technology make a researcher job interesting to examine the relationship between WhatsApp acceptance and job performance among the employee. This research is using Unified Theory of Acceptance and Use of Technology (UTAUT) as a model for succeeding this research. UTAUT model is contained of four variables which are effort expectancy (EE), performance expectancy (PE), social influence (SI) and facilitating conditions (FC). The method that have been used in this research is non-experimental which is used in the correlation research. The correlation is used to help and identify the variables of the relationship between WhatsApp acceptance and employee job performance among employee in the organizations. This research is using a questionnaire survey and is being distributed to 89 workers in Perbadanan Usahawan Nasional Berhad (PUNB), Kuala Lumpur. Based on the investigation, the relationship between effort expectancy, performance expectancy, social influence, facilitating conditions and job performance were existing and significant. All the Cronbach’s Alpha is acceptable and in a good score.